Toxicity Assessment of a Phase III Study Evaluating FEC-Doc and FEC-Doc Combined with Gemcitabine as an Adjuvant Treatment for High-Risk Early Breast Cancer: the SUCCESS-A Trial - Schröder, L.; Rack, B.; Sommer, H.; Koch, J. G.; Weissenbacher, T.; Janni, W.; Schneeweiss, A.; Rezai, M.; Lorenz, R.; Jäger, B.; Schramm, A.; Häberle, L.; Fasching, P. A.; Friedl, T. W. P.; Beckmann, M. W.; Scholz, C. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: This paper aims to evaluate the toxicity profile of additive gemcitabine to adjuvant taxane-based chemotherapy in breast cancer patients. Methods: Patients enrolled in this open-label randomized controlled Phase III study were treated with 3 cycles of epirubicin-fluorouracil-cyclophosphamide (FEC) chemotherapy followed by 3 cycles of docetaxel with those receiving 3 cycles of FEC followed by 3 cycles of gemcitabine-docetaxel (FEC-DG). 3690 patients were evaluated according to National Cancer Institute (NCI) toxicity criteria (CTCAE). The study medications were assessed by the occurrence of grade 3–4 adverse events, dose reductions, postponements of treatment cycles and granulocyte colony-stimulating factor (G-CSF) support. Results: No differences in neutropenia or febrile neutropenia were demonstrated. However, thrombocytopenia was significantly increased with FEC-DG treatment (2.0 vs. 0.5 %, p < 0.001), as was leukopenia (64.1 vs. 58.5 %, p < 0.001). With FEC-DG significantly more G-CSF support in cycles 4 to 6 (FEC-DG: 57.8 %, FEC-D: 36.3 %, p < 0.001) was provided. Transaminase elevation was significantly more common with FEC-DG (SGPT: 6.3 %, SGOT: 2 %), whereas neuropathy (1.2 %), arthralgia (1.6 %) and bone pain (2.6 %) were more common using FEC-D. Dose reductions > 20 % (4 vs. 2.4 %) and postponement of treatment cycles (0.9 vs. 0.4 %) were significantly more frequent in the FEC-DG arm. Eight deaths occurred during treatment in the FEC-DG arm and four in the FEC-D arm. Conclusion: The addition of gemcitabine increased hematological toxicity and was associated with more dose reductions and postponements of treatment cycles.
Keywords: adjuvant chemotherapy; gemcitabine; toxicity; hematological; breast cancer